Effects of Leadtree Seed (Leucaena leucocephala) Extract in Inhibiting the Increase of Postprandial Blood Glucose Level in Alloxan-induced Diabetic Rats - Pujangga, Ibnu Wadud; Nainggolan, Dorlina; Thadeus, Maria Selvester (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2019)
This research aimed to add evidence on the effect of white leadtree seed extract (Leucaena leucocephala) on postprandial blood glucose level on white male alloxan induced diabetic rats. This research was an experiment with pretest-posttest control group design. The subjects of this research were 25 white male rats, Wistar strain was divided into 5 groups. Group I was the positive control, which was treated with Acarbose, group II was the negative control, and group III, group IV, and group V were treatment groups and were given white leadtree seed extract of 1.5 g/kg of BW, 3.5 g/kg of BW, and 7.8 g/kg of BW respectively. Blood glucose level was checked before and two hours after treatment. The statistical analysis used one-way ANOVA and Bonferroni post hoc test. The result showed that there were no significant differences between group III, group IV, and group V and the positive control group (p<0.05). The best result of inhibition of the increase in blood glucose level was found in 7.8 g/kg of BW (group V) dosage group with average difference of 186.4 mg/dl. In conclusion, white leadtree seed extract could decrease two hour postprandial blood glucose level in white male alloxan-induced diabetic rats and a dosage of 7.8 g/kg of BW was shown to be the most effective.